The hurdle effect of osmotic pretreatment and high‐pressure cold pasteurisation on the shelf‐life extension of fresh‐cut tomatoes. (2nd March 2017) - Dermesonlouoglou, Efimia K.; Andreou, Varvara; Alexandrakis, Zacharias; Katsaros, George J.; Giannakourou, Maria C.; Taoukis, Petros S.
Abstract: Tomatoes are perishable products due to the activity of microorganisms and endogenous enzymes. The objective was to produce cut tomatoes with extended shelf life, using the combined hurdle effect of osmotic pretreatment (OD) and high pressure (HP), instead of a conventional one‐step thermal process. Samples were processed in a multicomponent osmotic solution at 35 °C, subsequently cold‐pasteurised in pack at 600 MPa and stored at 5–15 °C. Quality deterioration during isothermal and nonisothermal storage was kinetically modelled. Both OD process and OD‐HP combined process caused an increase in lycopene content that was well retained. Texture, colour and flavour of treated samples were evaluated as similar to fresh, with OD‐HP samples showing better retention during storage. Being microbiologically stable, shelf life of OD‐HP samples was limited by sensory deterioration, whereas OD samples were rejected due to eventual microbial growth. Shelf life of OD and OD‐HP samples was estimated at 77 and 181 days, respectively, at 5 °C. Abstract : The hurdle effect of osmotic pretreatment and high‐pressure cold pasteurisation on the shelf‐life extension of fresh‐cut tomatoes: Experimental design and main results.